105k views
3 votes
Solve 6y2-5y-6 = 0 using the quadratic formula.

A) y=- 3 over 2 or y =2 over 3

B) Y = -5 or y = -6

C) y or y=-2

D) y = 2 or y = 3​

User Chan Kim
by
4.3k points

2 Answers

5 votes

Answer:


y=(3)/(2) or
y=-(2)/(3)

Explanation:

We have the expression


6y^2-5y-6 = 0

For an equation of the form
ay^2 +by +c the quadratic formula is


y=(-b \± √(b^2 -4ac))/(2a)

In this case


a = 6\\b= -5\\c =-6


y=(-(-5) \± √((-5)^2 -4(6)(-6)))/(2(6))


y_1=(3)/(2)


y_2=-(2)/(3)

User Boris Treukhov
by
5.3k points
3 votes

Answer:

Ay=3 over 2 or y=-2 over 3

Explanation:

the quadratic formula: y={-b±√(b²-4ac)}/2a

In the equation 6y²-5y-6= 0, a=6, b=-5, c= -6

Substituting for the values in the formula we get:

{-(-5)±√[(-5²)-4(6)(-6)}/2(6)

{5±√169}12

={5±13}/12

(5+13)/12=3/2 or (5-13)/12= -2/3

User Desired Persona
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.